(untitled) (Scientific journal of the Fergana State University, 2023)
In this article, the essence of socio-pedagogical trainings in increasing the social activity of young people, their goals and objectives are highlighted. The results of the training conducted in cooperation of the methods that can be used in the trainings are analyzed.